Values of struggle in the novel by Ratih Kumala and its implication in learning literature in vocational high school - Marwati, Novi; Nurizzati, Nurizzati (BAHASTRA, 2025)
The purpose of this study is to describe the form of struggle values ​​contained in Ratih Kumala's novel and its use for literature learning in vocational schools. This study analyzes namely Gadis Kretek' and Saga dari Samudra.  Type of research is literary research with a descriptive analytical method. The instrument in this study is the researcher herself. Data analysis is classifying data on struggle values ​​in Ratih Kumala's novel, analyzing data, interpreting data, and compiling a learning design device for literary teaching materials. Based on the data analysis that has been done, two things can be concluded as follows. First, there are all indicators of the value of struggle in the novel Gadis Kretek by Ratih Kumala. The most dominant value in Gadis Kretek is the value of patience and unyielding spirit. Meanwhile, in the novel Saga dari Samudra, there are four values of struggle.  The most dominant value in the novel Saga dari Samudra is the value of self-sacrifice. There are more values ​​of struggle in the novel Gadis Kretek than in the novel Saga dari Samudra because the novel Gadis Kretek has a plot that predominantly depicts the characters' struggles in life. Second, the value of struggle in the novel by Ratih Kumala is closely related to life problems so that it can be utilized in literature learning, one of which is learning novel texts in class XII SMA / SMK. The utilization of struggle values ​​is done by integrating struggle values ​​as extrinsic elements in a novel.